APPLICATION PROBLEMS PRACTICE EXAM AT END OF SCHOOL (UAS) IN SENIOR HIGH SCHOOL 2 PAMULANG USING MACROMEDIA FLASH 8 - Defa Ganjar Suanggito; Syahril, SKom Syahril, SKom (Jurnal Sistem Informasi, 2009)
Along with the development of the age and the rapid technological and sophisticated,almost all layers of society in the world using a computer in various fields of work.Included in the educational activities in schools - the school.Applications to Problems Practice Exam School (UAS) in Senior High School 2Pamulang is used to minimize the time the questions, ease of checking problem andthe search for the ultimate value of which is computerized.Making Application to Problems Practice Exam School (UAS) in Senior High School2 Pamulang this using Macromedia Flash 8 application program and to relation usingPHP program.